The Jews, the Holocaust, and the Public
XVI, 365 p.
Keywords: This book explores the work and legacy of Professor David Cesarani OBE, a leading British scholar and expert on Jewish history who helped to shape Holocaust research, remembrance and education in the UK. It is a unique combination of chapters produced by researchers, curators and commemoration activists who either worked with and/or were taught by the late Cesarani. The chapters in this collection consider the legacies of Cesarani’s contribution to the discipline of history and the practice of public history. The contributors offer reflections on Cesarani’s approach and provide new insights into the study of Anglo-Jewish history, immigrants and minorities and the history and public legacies of the Holocaust.